Basic & clinical pharmacology - Katzung, Bertram G.; Trevor, Anthony J. (McGraw Hill Education, 2016)
A revised and updated textbook of pharmacology, providing expanded coverage of the nature of receptors and their interactions with drug and effector mechanisms including the newly characterized muscarinic and serotonin receptors. Drugs released onto the market in 1991 are also covered. These include adenosine for arrhythmias, ondansetron for vomiting, sumatriptan for migraine and implanted progestins for contraception.